2022
DOI: 10.1098/rsob.210241
|View full text |Cite
|
Sign up to set email alerts
|

Double nicking by RNA-directed Cascade-nCas3 for high-efficiency large-scale genome engineering

Abstract: New CRISPR-based genome editing technologies are developed to continually drive advances in life sciences, which, however, are predominantly derived from systems of Type II CRISPR-Cas9 and Type V CRISPR-Cas12a for eukaryotes. Here we report a novel CRISPR-n(nickase)Cas3 genome editing tool established upon a Type I-F system. We demonstrate that nCas3 variants can be created by alanine-substituting any catalytic residue of the Cas3 helicase domain. While nCas3 overproduction via plasmid shows severe cytotoxicit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Possibly, the Cas9 nuclease per se is toxic to the host cells. Similar observations have been reported for other bacteria (Zheng et al, 2020;Hao et al, 2022). Interesting, we found that the chromosome of P. alni Shahu encodes a native CRISPR-Cas system.…”
Section: Discussionsupporting
confidence: 91%
“…Possibly, the Cas9 nuclease per se is toxic to the host cells. Similar observations have been reported for other bacteria (Zheng et al, 2020;Hao et al, 2022). Interesting, we found that the chromosome of P. alni Shahu encodes a native CRISPR-Cas system.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, the use of the Cas3 K39A variant in combination with a donor template enhanced editing efficiency. Recently, a Cas3 helicase variant of the Zymomonas mobilis type I-F system was applied endogenously to carry out genome editing with high efficiency (46). In that study, crRNA was used to target each strand of the target, resulting in "dual nicking" of the target gene.…”
Section: Discussionmentioning
confidence: 99%
“…In Z. mobilis , gene deletion and insertion and single base substitution can be realized with 100% efficiency, but deletion of large genomic fragments such as a 10-kb fragment was only achieved with less than 50% efficiency [80] . To increase the deletion efficiency for large genomic fragments, a recent study created an nCas3 variant by replacing the catalytic residues with alanine and showed that the I-F Cascade-nCas3 enabled gene insertion, gene deletion, single base substitution and deletion of one or even two large genomic fragments at once with almost 100% efficiency [81] .…”
Section: Type I Crispr-cas-mediated Gene Editingmentioning
confidence: 99%